The syrphids of Serra do Courel, Northern Spain and description of a new Cheilosia Meigen species (Diptera: Syrphidae) - Ricarte, Antonio; Rotheray, Graham E.; Lyszkowski, Richard M.; Hancock, E. Geoffrey; Hewitt, Stephen M.; Watt, Kenneth R.; Horsfield, David; Macgowan, Iain (Zootaxa, 2014)
The syrphids (Syrphidae) of Serra do Courel, a mountainous locality of just over 20,000ha at the west end of the Cantabrian Mountains, northern Spain are poorly known. The Scottish based, Malloch Society visited the locality in May 2012 and collected a total of 462 specimens of 98 syrphid species and 36 genera. These represent the first syrphid records from Serra do Courel. The area has many meadows and small woodlands or ‘soutos’ and these habitats combined were the most productive, 69 spp. recorded. Cheilosia lucense Ricarte sp. nov. is described from Courel and compared with other species of the alpina group. Six other syrphid species were new to the Iberian Peninsula, three of which belong to the saproxylic genus, Brachyopa. In common with studies elsewhere in the Cantabrian Mountains, Cheilosia was the most diverse genus and 21 species were recorded. The syrphid fauna of the Cantabrian Mountains includes 203 species of which 24 are here added and a species checklist provided.